The development of a novel FM nanoadsorbent for heavy metal remediation in polluted water - Khairiah Lubis (Elsevier, 2022)
Heavy metal pollution in the environment is a severe issue. Heavy metals directly impact people's lives since they accumulate in the food chain, even in low amounts. Some heavy metals were found to have polluted the water, exceeding the dangerous limits for life. A nanoadsorbent is needed to remediate heavy metals. Fe3O4 magnetic nanoadsorbent has been synthesized without and with additional materials using a combination method of coprecipitation and milling, namely Fe3O4 Magnetic (FM), Fe3O4 Magnetic/Activated Carbon (FMAC), Fe3O4 Magnetic/Chitosan (FMCH), and Fe3O4 Magnetic/Glutaraldehyde (FMG). According to the AAS characterization results, the adsorption percentage of FM nanoadsorbent without additives was higher than that of other materials with additives. Structural characterization showed the crystal size of Fe3O4 magnetic without additives with a range of 11 nm. The surface morphology characterization showed no aggregation, and the maximum percentage of Fe3O4 magnetic purity without additional material was 89.26%.% Adsorption is affected by contact time, stirring speed, and the pH of the solution. Optimum% adsorption occurred at a contact time of 120 min, a stirring speed of 200 rpm, and a solution pH of 7 (neutral) 99.27%. The novelty Fe3O4 magnetic nanoadsorbent without additional material is more effective in remediating polluted water.